Perceptions of patient disease burden and management approaches in systemic mastocytosis: Results of the TouchStone Healthcare Provider Survey. Issue 20 (23rd August 2022) - Mesa, Ruben A.; Sullivan, Erin M.; Dubinski, David; Carroll, Brittany; Slee, Valerie M.; Jennings, Susan V.; Finnerty, Celeste C.; Bohannon, Linda S.; Mathias, Susan D.; Lahue, Betsy J.; Castells, Mariana C.
Abstract : Background: Systemic mastocytosis (SM) is a rare clonal neoplasm driven by the KIT D816V mutation and has a broad range of debilitating symptoms. In this study, the authors evaluated SM disease perceptions and management strategies among US health care providers (HCPs). Methods: Hematologist/oncologist (H/O) HCPs and allergist/immunologist (A/I) HCPs who were treating four or more patients with SM completed an online, 51‐item TouchStone HCP Survey, which queried provider characteristics, perceptions of disease burden, and current management. Descriptive analyses by specialty and SM subtype were performed. Results: Of 304 HCPs contacted, 111 (37%) met eligibility criteria, including 51% A/I specialists and 49% H/O specialists. On average, the HCPs had 14 years of practice experience and cared for 20 patients with SM. A/I HCPs saw more patients with nonadvanced SM (78%) compared with H/O HCPs, who saw similar proportions of patients with nonadvanced SM (54%) and advanced SM (46%). HCPs reported testing 75% of patients for the KIT D816V mutation and found an estimated prevalence of 47%. On average, HCPs estimated 8 months between symptom onset and SM diagnosis. HCPs reported that 62% of patients with indolent SM felt depressed or discouraged because of symptoms. In terms of treatment goals for SM, both types of specialists prioritized symptom improvement for nonadvanced SM and improved survival for advanced SM while also prioritizing improving patient quality of life. Conclusions: Both A/I and H/O specialists highlighted unmet needs for patients with SM. The HCPs surveyed reported a lower rate of KIT D816V mutations and a perceived shorter time between symptom onset and SM diagnosis compared with published estimates. Lay summary: Specialists treating systemic mastocytosis (SM) completed a 51‐item questionnaire about their clinical practices and perceptions of disease impact. The study included 111 hematology, oncology, allergy, and immunology physicians. Physicians reported that most patients had nonadvanced disease, yet SM symptoms significantly disrupted their patients' lives. Physicians estimated that SM is diagnosed within months of symptom onset, in contrast with published reports of years' long delays reported by patients with SM. This study identified unmet needs that can inform educational and patient management priorities in this rare disease. Abstract : Physician specialists who manage patients with systemic mastocytosis reported that their patients experienced life‐threatening anaphylaxis and reduced quality of life. This study identified unmet needs that can inform educational and patient management priorities in this rare disease.